Aproximação de polo para partículas pseudoescalares - Vaccani, Gustavo Antonio Pires (2022)
In elementary particle physics, some detected hadrons contain complicated internal structures and complex external interactions. Based on this, increasingly sophisticated approaches and methods are needed to describe particle physical properties and their interactions. Exploring the quantum field theory within light-front dynamics, the work studies the elastic electromagnetic form factors of pseudoscalar mesons using a symmetric vertex function and the pole approximation approach. Furthermore, other observables can be built from these electromagnetic form factors studies, for example, the mean-square charge radius and weak decay constant. Moreover, this work investigates the reliability of the pole approximation approach to the exact values of electromagnetic form factors using only a few poles of the Feynman amplitudes, simplifying the calculations without the direct dependence of external propagators. The consequences of that approach for all the observables are also compared with the experimental data. Once calculations of the observables and the pole approximation approach studies have been satisfactory for the pion experimental data, the work is implemented for other more complex meson structures. In this way, the pole approximation approaches can simplify calculations of electromagnetic form factors, at first, for more complex pseudoscalar meson structures, other types of ansatz for regulator vertex functions, or more sophisticated dynamical models based on solutions of a Bethe-Salpeter equation.